Kazakhstani librarians explore emerging global trends in university library development - Sarsembinova (Сарсембинова), Aliya (Алия) (Library Connect/Elsevier, 2014)
To advance its research base, Kazakhstan is actively working to enhance international standards and practices within its academic libraries. In support of this mission, Nazarbayev University and Elsevier hosted the second annual Library Connect event on June 11-12 in Astana devoted to the issues of developing academic libraries.
Keywords: library development; libraries, Kazakhstan; Nazarbayev University Library; Nazarbayev University Scientific Library; higher education, Kazakhstan; library; Kazakhstani librarians